Legal Analysis of the Implementation of the Ten Steps to Successful Breastfeeding in Government Regulation Number 28 of 2024 to Support the Exclusive Breastfeeding Program in Indonesia - Dolesgit, Ni Made Garnis; Parsa, I Wayan; Astuti, Ika Widi; Winata, I Gede Sastra (Babali Publisher, 2025)
Introduction: Efforts to advance the welfare of Indonesian society require the development of quality human resources. However, health issues such as stunting and obesity in children can hinder these aspirations, partly due to suboptimal breastfeeding from birth. Although there has been a significant increase in exclusive breastfeeding, there are still obstacles in its implementation, such as a lack of family support and violations of the International Code of Marketing of Breastmilk Substitutes. This study aims to analyze the implementation of the Ten Steps to Successful Breastfeeding (TSSB) advocated by WHO and UNICEF in Government Regulation Number 28 of 2024 to support the Exclusive Breastfeeding program in Indonesia.Method: This study used a descriptive-analytical method with a normative juridical approach, referring to Government Regulation Number 28 of 2024 concerning the Implementation Regulation of Law Number 17 of 2023 concerning health.Result: Almost all TSSB and all the rules of the International Code of Marketing of Breastmilk Substitutes have been included in the articles to subsequently serve as protection against inappropriate promotion of formula milk for infants and to achieve Exclusive Breastfeeding.Conclusion: It is necessary to immediately create specific follow-up regulations regarding the safe provision and administration of donor breast milk for infants in healthcare institutions and a sustainable data monitoring and management system.